Predictors of Superior Firm Performance: a Conceptual Model of Tourism Small Medium Enterprises in Saudi Arabia - Samad, Sarminah; Alrubaishi, Dalal; Alghafis, Rasha (International Journal of Engineering and Technology, 2018)
Deriving from previous literatures, the theories of Resource-based View and Dynamic Capability was used in this study to propose a model that examines the predictors of the performance of Small and Medium Enterprises (SMEs). Accordingly, it will examine the influence of corporate management strategy on the performance of SMEs. It will analyze the extent to which innovative dynamic capabilities would enhance the relationship between corporate management strategy and performance of SMEs. It will also examine the extent innovation leadership serves as the moderator factor on the link between corporate management strategy and performance of SMEs. Finally, this paper intends to recommend a model of performance management system for the performance of tourism SMEs in Saudi Arabia. The study will employ a quantitative approach among selected tourism SMEs in Saudi Arabia. SPSS and AMOS (SEM) will be used to analyse the data obtained. Findings from this study will serve as a guideline for policy and decision makers in both private and public organizations.